Mudanças comerciais e estruturais no mercado internacional de celulose: efeitos nos fluxos e preços - Oliveira, Antônio Donizette de; Silva, Orlando Monteiro da; Rezende, José Luiz Pereira de (Estudos Econômicos (São Paulo), 1997)
The present study analyses the evolution ofmarket prices and flows of the international pulp market, considering the chief exporting and importing countries. A model for pulp international market was built assuming that goods from differents countries are not homogeneous, from the consumer's point the view. The model is simulated for various shocks in exogenous variables, such as changes of demand and supply, shifters and of pulp import tariffs. The results suggest thatthe exogenous changes thatstimulate pulp demand growth in Japan and Europe benefit all exporting countries, with a higher advantage for Canada and the USA. Pulp taxation by the European marketis harnful to all exporting countries, due to price and trade flow lowering with that market. The increase in pulp production by Canada and Brazil reduce the pulp exportincome of these countries and the USA more than the European pulp taxation.